2022
DOI: 10.1161/jaha.121.024746
|View full text |Cite
|
Sign up to set email alerts
|

Same‐Day Discharge After Transcatheter Aortic Valve Implantation: Insights from the Nationwide Readmission Database 2015 to 2019

Abstract: Background There is a paucity of data on the feasibility of same‐day discharge (SDD) following transcatheter aortic valve implantation (TAVI) at a national level. Methods and Results This study used data from the Nationwide Readmission Database from the fourth quarter of 2015 through 2019 and identified patients undergoing TAVI using the claim code 02RF3. A total of 158 591 weighted hospitalizations for TAVI were included in the analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Several studies have reported favorable outcomes with same‐day discharge in carefully selected patients undergoing TAVR. 17 , 18 , 19 , 20 However, a recent report from the Nationwide Readmission Database (n=158 591) revealed that same‐day discharge was performed in only 0.6% of patients undergoing TAVR from 2015 to 2019. 20 Similarly, in a recent multicenter study across 7 international TAVR programs only 5.9% were deemed eligible for same‐day discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported favorable outcomes with same‐day discharge in carefully selected patients undergoing TAVR. 17 , 18 , 19 , 20 However, a recent report from the Nationwide Readmission Database (n=158 591) revealed that same‐day discharge was performed in only 0.6% of patients undergoing TAVR from 2015 to 2019. 20 Similarly, in a recent multicenter study across 7 international TAVR programs only 5.9% were deemed eligible for same‐day discharge.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 , 19 , 20 However, a recent report from the Nationwide Readmission Database (n=158 591) revealed that same‐day discharge was performed in only 0.6% of patients undergoing TAVR from 2015 to 2019. 20 Similarly, in a recent multicenter study across 7 international TAVR programs only 5.9% were deemed eligible for same‐day discharge. 18 These findings suggest that same‐day discharge is unlikely to be widely adopted, especially with this strategy being feasible only for cases performed earlier in the day.…”
Section: Discussionmentioning
confidence: 99%
“…The number of TAVR procedures is rapidly increasing, and the continuous expansion of the population deemed suitable for TAVR [ 10 , 11 ] has corresponded with an impressive constant evolution in TAVR devices and materials. Indeed, these advances have significantly reduced periprocedural complications, making it safe to shorten hospital stay and improve long-term outcomes [ 12 , 13 ]. Moreover, these progresses have resulted in a wide armamentarium at our disposal, including bioprostheses presenting different dimensions, designs, and deliverability, providing the opportunity to select a device based on each patient’s clinical and anatomic characteristics.…”
Section: Introductionmentioning
confidence: 99%